2000
DOI: 10.1074/jbc.m001000200
|View full text |Cite
|
Sign up to set email alerts
|

Biological Function and Site II Ca2+-induced Opening of the Regulatory Domain of Skeletal Troponin C Are Impaired by Invariant Site I or II Glu Mutations

Abstract: To investigate the roles of site I and II invariant Glu residues 41 and 77 in the functional properties and calcium-induced structural opening of skeletal muscle troponin C (TnC) regulatory domain, we have replaced them by Ala in intact F29W TnC and in wild-type and F29W N domains (TnC residues 1-90

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 75 publications
(117 reference statements)
4
18
0
Order By: Relevance
“…K d s for magnesium binding were 2.2 mM and 0.5 mM for TN-L15 and TN-humTnC, respectively. Site-directed mutagenesis has been used extensively to study ligand-binding properties and conformational change within troponin C. Therefore, we inactivated individual EF-hands systematically by exchanging crucial aspartate or glutamate residues within the binding loops with either alanine or glutamine (20,21). The mutation D107A (20), by which the third, Cterminal EF-hand was inactivated within TN-L15, resulted in an indicator with reduced calcium affinity, in agreement with published results.…”
Section: Ratiometric Indicators With New Calcium-binding Moieties-itsupporting
confidence: 74%
“…K d s for magnesium binding were 2.2 mM and 0.5 mM for TN-L15 and TN-humTnC, respectively. Site-directed mutagenesis has been used extensively to study ligand-binding properties and conformational change within troponin C. Therefore, we inactivated individual EF-hands systematically by exchanging crucial aspartate or glutamate residues within the binding loops with either alanine or glutamine (20,21). The mutation D107A (20), by which the third, Cterminal EF-hand was inactivated within TN-L15, resulted in an indicator with reduced calcium affinity, in agreement with published results.…”
Section: Ratiometric Indicators With New Calcium-binding Moieties-itsupporting
confidence: 74%
“…However, Pearlstone et al (57) highlighted the difficulty in conferring biological significance to cooperativity inferred from Ca 2ϩ titrations using indirect spectroscopic methods. This is mainly because of Hill coefficients greater than unity which were predicted for processes known to be related to the filling of only one site (57). Although our fluorescence data led in some cases to predicted Hill coefficients different from unity (Table II), we consider that there is no secure reason to assume all those values as real indications of positive or negative cooperativity.…”
Section: Ca 2ϩ Binding To the Regulatory Sites Of Tncmentioning
confidence: 42%
“…Pearlstone et al (57) suggested that this decrease is associated with opening of the N-domain, based on the characteristics of cardiac TnC (cTnC) and the E41A mutant of TnC. These proteins show neither the CD band decrease nor the opening of N-domain upon calcium binding (53,55).…”
Section: Ca 2ϩ Binding To the Regulatory Sites Of Tncmentioning
confidence: 99%
“…Preparation of cTnC"WT" and fsTnC-The pET3a⅐cTnC and pET3a⅐fsTnC constructs have been described previously (15,16). For the present study, the Cys-34 and Cys-83 codons (TGC) of pET3a⅐cTnC were mutated to Ser codons (AGC) using paired 31-and 37-mer oligonucleotides, respectively (Stratagene).…”
Section: Methodsmentioning
confidence: 99%